Sleep Disturbances in OEF/OIF/OND Veterans: Associations with PTSD, Personality, and Coping - Lind, Mackenzie J. (J Clin Sleep Med, 2017)
STUDY OBJECTIVES: Sleep disturbances are well documented in relation to trauma exposure and posttraumatic stress disorder (PTSD), but correlates of such disturbances remain understudied in veteran populations. We conducted a preliminary study of sleep disturbances in Operation Enduring Freedom, Operation Iraqi Freedom, and Operation New Dawn veterans (n = 133; mean [standard deviation] age = 29.8 [4.7] y). METHODS: Veterans were assigned to one of three groups based on responses to the Clinician Administered PTSD Scale: control (no trauma-exposure [TE] or PTSD), TE, and PTSD. Sleep disturbance was assessed using the Pittsburgh Sleep Quality Index (PSQI). Measures of resilience, trauma load, personality, coping, alcohol use, and mild traumatic brain injury were also assessed via self-report. RESULTS: The PTSD group had significantly more disturbed sleep (PSQI global score mean = 8.94, standard deviation = 3.12) than control (mean = 5.27, standard deviation = 3.23) and TE (mean = 5.34, standard deviation = 3.17) groups, but there were no differences between TE and control. The same pattern emerged across most PSQI subscales. Results of linear regression analyses indicated that current smoking, Army (versus other military branches), neuroticism, and using substances to cope were all significant correlates of higher sleep disturbance, whereas post-deployment social support was associated with less sleep disturbance. However, when combined together into a model with PTSD status, only neuroticism and substance use coping remained significant as predictors of more disturbed sleep. CONCLUSIONS: These initial findings suggest that TE itself may not be an independent risk factor for disturbed sleep in veterans, and that neurotic personality and a tendency to cope by using substances may partially explain sleep disturbance, above and beyond a diagnosis of PTSD. CITATION: Lind MJ, Brown E, Farrell-Carnahan L, Brown RC, Hawn S, Berenz E, McDonald S, Pickett T, Danielson CK, Thomas S, Amstadter AB. Sleep disturbances in OEF/OIF/OND veterans: associations with PTSD, personality and coping. J Clin Sleep Med 2017;13(2):291–299.